La historiografía occidental y sus desarrollos en Colombia (2010)
This paper highlights the Occidental Historiography’s develop in the last century, their projections in the present one and the way of how this science has been applied to the Colombian case, all of these because we have to know the real role of the historian in the present times. Considering the main historiography’s schools and their insertion inside de social and scientific context througth the time, following to close the experts opinions about the topic in discussion and explaining that besides the history’s times are totally different these always are going to be connected.